Changes during chilled storage of whole tilapia and short-term frozen storage of tilapia fillets - Viegas, Elisabete Maria MacEdo; Barbieri de Carvalho, Maria Regina [UNESP]; Campagnoli de Oliveira Filho, Paulo Roberto; Kirschnik, Peter Gaberz; Aiura, Felipe Shindy; Vargas, Sheyla Cristina (Taylor & Francis, 2013)
This study evaluated the physicochemical changes in Nile tilapia (n = 82, 373.71 ± 61.91 g) refrigerated for up to 92 h and in the frozen fillets. The tilapias were captured with nets, slaughtered by ice and water shock (1:1) in a temperature of approximately 2°C for 30 min, and stored refrigerated at 4°C in polystyrene boxes containing ice. The fish were filleted, and filets were weighed and frozen. The drip loss and protein were determined after 23 days of frozen storage. After 4 h of storage, all fish were in full rigor mortis. The pH of the muscles decreased for up to 45 h of the storage period. The fillets obtained from tilapia stored for more than 72 h lost more weight and protein. Thus, the filleting or processing of tilapia should be done before 72 h of cold storage, since deterioration of the fish starts to occur after this period. Copyright © Taylor & Francis Group, LLC.
Keywords: Drip loss; Oreochromis niloticus; Quality; Rigor mortis; Shelf life; Chilled storage; Physico-chemical changes; Storage periods; Tilapia fillets; Cold storage; Image quality; Polystyrenes; Proteins; Fish